Analysis of Local Original Income Components in Gorontalo Province - P.I Thalib, Nikmatuljannah; Mopangga, Herwin; Dai, Sri Indriyani S. (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This Study aims to analyze the Effect of Local Taxes, Local revenues, and Results of Regional Asset Management on Local Revenue in Gorontalo Province. The data used in this study are secondary data sourced from the Directorate General of Balance, Ministry of Finance of the Republic of Indonesia, obtained from 6 Regencies/Cities in Gorontalo Province. This study uses Multiple Linier Regression Analysis of Panel Data using the Fixed Effect Model (FEM). The results showed that 1. Local Taxes have a Positive and significant effect on Local Revenue. This means that every increase in Local Taxes will increase the value of Local Revenue in Gorontalo Province. 2) Local Retributions have a Positive and significant effect on Local Revenue. This means that every increase in Regional Retribution will increase the value of Regional Original Income in Gorontalo Province. 3) The results of Regional Asset Management do not have a significant effect on Regional Original Income. This means that every increase in Regional Retribution cannot increase the value of Regional Original Income in Gorontalo Province.